Interactive Associations of Neuropsychiatry Inventory-Questionnaire Assessed Sleep Disturbance and Vascular Risk on Alzheimer’s Disease Stage Progression in Clinically Normal Older Adults - Bubu, Omonigho M.; Williams, Ellita T.; Umasabor-Bubu, Ogie Q.; Kaur, Sonya S.; Turner, Arlener D.; Blanc, Judite; Cejudo, Jaime Ramos; Mullins, Anna E.; Parekh, Ankit; Kam, Korey; Osakwe, Zainab T.; Nguyen, Ann W.; et al. (Frontiers in Aging Neuroscience, 2021)
Background: To determine whether sleep disturbance (SD) and vascular-risk interact to promote Alzheimer’s Disease (AD) stage-progression in normal, community-dwelling older-adults and evaluate their combined risk beyond that of established AD biomarkers. Methods: Longitudinal data from the National Alzheimer's Coordinating Center Uniform-Dataset. SD data (i.e. SD+ vs. SD-), as characterized by the Neuropsychiatric Inventory-Questionnaire, were derived from 10,600 participants at baseline, with at-least one follow-up visit. A subset (n=361) had baseline cerebrospinal fluid (CSF) biomarkers and MRI-data. The Framingham Heart Study general cardiovascular disease (FHS-CVD) risk-score was used to quantify vascular-risk. Amnestic Mild Cognitive-Impairment (aMCI) diagnosis during follow-up characterized AD stage-progression. Logistic mixed-effects models with random intercept and slope examined the interaction of NSD and vascular-risk on prospective aMCI diagnosis. Results: Of the 10,600 participants, 1017 (9.6%) reported SD and 6572 (62%) were female. The overall mean (sd) age was 70.5 (6.5), and follow-up time was 5.1 (2.7) years. SD and the FHS-CVD risk-score were each associated with incident aMCI (aOR: 1.42 and aOR: 2.11, P < .01 for both). The interaction of SD and FHS-CVD risk-score with time was significant (aOR: 2.87, P < .01) suggesting a synergistic effect. SD and FHS-CVD risk-score estimates remained significantly associated with incident aMCI even after adjusting for CSF (Aβ, T-tau, P-tau) and hippocampal volume [n=361] (aOR: 2.55, P < .01), and approximated risk-estimates of each biomarker in the sample where data was available. Conclusions: Clinical measures of sleep and vascular-risk may complement current AD biomarkers in assessing risk of cognitive-decline in older-adults.